Fashion loanwords in the 19th century - Vázquez-Amador, María (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This work aims to study the loanwords in the field of textile terminology during the 19th century, through the analysis of a fashion magazine. The languages of origin, their formal typology, the thematic areas and their acceptance in the dictionaries of the Royal Spanish Academy were examined. Forty-five loanwords were located, mainly from French and English. The loanwords were non adapted, adapted or partially adapted. A high percentage was admitted in at least one of dictionaries by the Royal Spanish Academy and are still valid in the current edition. These data show that these loanwords were novel concepts that filled a gap in our language and thus have remained in it.
Keywords: Linguistic loanwords; textile lexicon; fashion; 19th century